2021
DOI: 10.1161/jaha.121.023535
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐Converting Enzyme Inhibitors, Angiotensin II Receptor Blockers, and Outcomes in Patients Hospitalized for COVID‐19

Abstract: Background Use of angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers (ACEi/ARB) is thought to affect COVID‐19 through modulating levels of angiotensin‐converting enzyme 2, the cell entry receptor for SARS‐CoV2. We sought to assess the association between ACEi/ARB, biomarkers of inflammation, and outcomes in patients hospitalized for COVID‐19. Methods and Results We leveraged the ISIC (International Study of Inflammation in COVID‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
17
2
Order By: Relevance
“…Some studies have shown a significant association between ACEi or ARB use and risk of SARS-CoV-2 infection and severity of health outcomes. (21, 22) In contrast to that, our study did not find any association, positive or negative, between ACEi or ARB use and serostatus. This suggests that use of ACEi or ARB may not affect vaccine efficacy, even if their use has the potential to influence risk of disease or its severity.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have shown a significant association between ACEi or ARB use and risk of SARS-CoV-2 infection and severity of health outcomes. (21, 22) In contrast to that, our study did not find any association, positive or negative, between ACEi or ARB use and serostatus. This suggests that use of ACEi or ARB may not affect vaccine efficacy, even if their use has the potential to influence risk of disease or its severity.…”
Section: Discussioncontrasting
confidence: 99%
“…Leisman et al and Ofosu-Barko et al reported that angiotensin-II treatment was associated with rapid improvement in multiple physiologic indices [38, 51]. The rationale for angiotensin-II therapy is based on decreasing the expression of the ACE2 receptors, which can reduce the entry of the COVID-19 virus into cells [61, 62]. However, the progressive loss of ACE2 shifts the system to an overall higher angiotensin level due to the impaired ability of ACE2 to degrade it, which may explain the initial hemodynamic stability of patients with COVID-19 [63].…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 An increase in suPAR levels can be triggered by various stimuli, including SARS‐CoV‐2, and suPAR is highly expressed in lung tissue, 18 which may be critical for disease progression. Indeed, suPAR has been recently implicated in the evolution of COVID‐19 and its associated complications 12 , 19 , 20 and represents the inflammatory biomarker that is most reflective of the hyperinflammatory state in patients with comorbidities. 3 , 12 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…16,17 An increase in suPAR levels can be triggered by various stimuli, including SARS-CoV-2, and suPAR is highly expressed in lung tissue, 18 which may be critical for disease progression. Indeed, suPAR has been recently implicated in the evolution of COVID-19 and its associated complications 12,19,20 and represents the inflammatory biomarker that is most reflective of the hyperinflammatory state in patients with comorbidities. 3,12,21 The WHO-CPS score was developed in response to the needs of the rapidly evolving COVID-19 outbreak, including a measure of viral burden, a measure of patient survival, and a measure of patient progression.…”
Section: Discussionmentioning
confidence: 99%